Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea: Dryopidae) - Barr, Cheryl B.; Shepard, William D. (Zootaxa, 2020)
The history and original concept of Parygrus Erichson, 1847, is reviewed, the genus is redescribed, and the status of the type species, P. erichsoni Waterhouse, 1876, is clarified. The four original species are reviewed, with photographs provided for the type specimens of P. angustatus Grouvelle, 1896, P. elateroides Grouvelle, 1896, and P. erichsoni, and a non-type of P. parallelus (Grouvelle, 1890). The holotype of P. parallelus is apparently missing. The female holotype of P. erichsoni is redescribed. An associated male P. erichsoni specimen is compared with the holotype and the male genitalia are described and illustrated. General descriptions and provisional diagnoses are given for P. angustatus, P. elateroides and P. parallelus. Five new species (P. guarani new species, P. lengua new species, P. maya new species, P. quechua new species, P. zamuco new species) are proposed, illustrated, and their geographic distributions mapped. For the first time, the male genitalia of Parygrus species are described and illustrated. A provisional key to the species and an updated key to the Neotropical genera of Dryopidae are provided.